Cost Analysis Study of Topical Anti-Acne Drugs Currently Available in Indian Pharmaceutical Market - Neelomjyoti Gohain; Hiteswar Saikia; Meghali Chaliha (Journal of Pharmaceutical Research)
Acne vulgaris is a chronic inflammatory skin disease that affects approximately 90% individuals between puberty and 30 years of age at some point with peak prevalence in adolescence. According to Global Burden of Disease study conducted in 187 countries in 2010, acne is among top ten most prevalent disease worldwide and skin conditions are top cause of years lived with disability. The aim of the study was to analyze cost variations of different brands of topical medications used in Acne vulgaris in India. This analytical study was conducted in the Department of Pharmacology at Assam Medical College and Hospital over a period of 3 months. ‘‘Current Index of Medical Specialities (CIMS)’’ April - July, 2023 and “Drug Today India April –July 2023’’ drug manuals were used to compare cost of different formulations of topical acne medications. Drugs manufactured by only 1 company were excluded. Cost ratio (Maximum cost/ Minimum cost) and percentage cost variation ([Max cost – Min cost/ Min cost] *100) were calculated. For single preparations, the percentage cost variation was maximum for Clindamycin 1% 20 grams gel (1126.66%) with maximum cost ratio followed by Tretinoin 20 gm 0.025% (cream) 721.428. Percentage cost variation was minimum with Adapalene 0.1 % cream 15gm (32.69). Among the combination topical drugs, the percentage cost variation was maximum for Clindamycin 1% + Adapalene 0.1% 15 grams gel (1843.589) and it had maximum cost ratio of 19.43. Percentage cost variation was minimum with combination of Benzoyl Peroxide 2.5% + Clindamycin 1% 20gm gel(41.025).This study highlights price variation among different brands of drugs in CIMS, Drug Today and Pharma Sahi Daam app. Keywords Cost Analysis, Acne vulgaris, Percentage CostVariation, Pharma Sahi Daam